تقييم نظام الموازنة المطبق في المشافي الحكومية وإمكانية تطبيق موازنة الأنشطة دراسة ميدانية في محافظة اللاذقية - نادر, نهاد; حيدر, وئام (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت هذه الدراسة إلى تقييم نظام الموازنة المطبق في المشافي الحكومية في محافظة اللاذقية، والبحث في مدى توافر الإمكانيات اللازمة لتطبيق موازنة الأنشطة.ولتحقيق أهداف الدراسة صممت استبانة شملت أسئلتها مختلف الجوانب المتعلقة بالموازنة القائمة، ومدى توافر الإمكانيات الإدارية والمالية والفنية والبيئية. حيث وزعت الاستبانة على موظفي القسم المالي والإداري في مديرية الصحة إضافة إلى موظفي المشافي الحكومية التابعة لوزارة الصحة في المحافظة. وقد خلصت الدراسة إلى مجموعة من النتائج أهمها أن الموازنة المطبقة في المشافي لا تلبي الاحتياجات المطلوبة، وأنه توجد العديد من المعوقات والمشاكل التي تواجه إمكانية تطبيق موازنة الأنشطة في المشافي محل الدراسة. وبناءً على النتائج أوصت الباحثة بضرورة تهيئة البنية التحتية الملائمة لتطبيق موازنة الأنشطة بتفعيل استخدام التكنولوجيا الحديثة، وتوفير مصادر التمويل اللازمة إضافة إلى تهيئة الظروف السياسية والاقتصادية والقانونية اللازمة لتطبيق موازنة الأنشطة؛ وذلك للاستفادة من مزاياها في إدارة التكلفة واستغلال الموارد بكفاءة عالية.This study aimed to evaluate the budget applied in the government hospitals in Latakia, and research into the possibility of the application of (Activity-Based Budgeting). To achieve the objectives of the study are designed questionnaire include questions related to various aspects of the existing budget, and the availability of administrative, financial, technical and environmental potential. Where the questionnaire was distributed on the financial and administrative department in the Directorate of Health staff in addition to the six staff of government hospitals in the province. The study concluded that the most important set of results, that the budget applied in hospitals do not meet the requirements, and that there are many obstacles and problems facing the possibility of applying the (Activity-Based Budgeting) in hospitals under study. Based on the findings the researcher recommended the need for appropriate infrastructure to create for the application of (Activity-Based Budgeting) to activate the use of modern technology, and provide sufficient resources as well as create the necessary political, economic and legal conditions for the application of (Activity-Based Budgeting) to take advantage of their advantages in cost management and exploitation of resources.